Characterization of the Isosteroidal Alkaloid Chuanbeinone from Bulbus of Fritillaria pallidiflora as Novel Antitumor Agent In Vitro and In Vivo - Wang, Dongdong; Li, Zu; Zhang, Li; Atanasov, Atanas G.; Wang, Shu (Planta Medica, 2016)
Bulbus of Fritillaria pallidiflora, the dried bulb of F. pallidiflora, is widely used in Chinese folk medicine due to its powerful biological activities. The aim of this study was to investigate in vitro and in vivo antitumor activity of different fractions and isosteroidal alkaloids from bulbus of F. pallidiflora and clarify its putative mechanism of antitumor activity. Firstly, we assayed in vitro antitumor effects of different fractions from bulbus of F. pallidiflora and found that chloroform extracts and purified total alkaloids of bulbus of F. pallidiflora showed higher cytotoxic activity than other tested extracts. We further isolated four main alkaloids, chuanbeinone, imperialine-β-N-oxide, isoverticine and isoverticine-β-N-oxide, from the total alkaloids of bulbus of F. pallidiflora and found that they display significant cytotoxicity, whereby chuanbeinone showed the highest activity against Lewis lung carcinoma cells. Moreover, we found that chuanbeinone induced S phase arrest and further increased apoptosis of Lewis lung carcinoma cells. The results of Western blotting experiments showed that the expression of the antiapoptotic Bcl-2 was reduced by chuanbeinone treatment, while the proapoptotic protein Bax and caspase-3 were increased. Moreover, we investigated the in vivo antitumor activity of chuanbeinone and characterized its putative antitumor mechanism of action by the TUNEL assay and by histological and immunohistochemical analyses. Our results showed that chuanbeinone exhibited significant antitumor activity in vivo, while notably inhibiting tumor angiogenesis and inducing apoptosis characterized by an increased expression of caspase-3. Our findings show that chuanbeinone exhibits significant antitumor activity in vitro and in vivo, and points to possible therapeutic potential for this compound as well as for its natural source, bulbus of F. pallidiflora.
Keywords: Fritillaria pallidiflora; Liliaceae; antitumor activity; caspase-3; cell cycle; microvessel density